Plea bargaining in Russia: the role of defence attorneys and the problem of asymmetry - Moiseeva, Ekaterina Nikolaevna (International journal of comparative and applied criminal justice, 2017)
This research examines pretrial and trial negotiations in Russia’s criminal justice system. It corroborates the statement that plea bargaining is a norm until it preserves the latter element - “bargaining.” Negotiation skills are especially important for defence attorneys who take a mediator position between the legal community and civil society. The author claims that the nature of negotiations in Russia’s criminal justice system is no different from that of other countries. Institutionally the weakest professional group in the Russian legal field, defence attorneys manage to play on the weaknesses of law enforcers and balance their own bargaining position. Yet, accusatory bias of Russian criminal process, managerial problems in law-enforcement agencies, and ineffective regulation of the appointed counsel system create a fertile ground for “shady” practices of defenders. In legal jargon, this phenomenon is labelled as “pocket defence attorneys” - a concept that embraces those actions of appointed counsels that benefit state officials but not defendants. Dependence of appointed defence attorneys on law enforcers is a top-of-mind problem for Russia. An examination of such extreme cases can shed some light on the extent to which organisational context shapes the way lawyers dispense justice elsewhere.